Digital Options for 1st Year University Student Education Support and Enhance Motivation - Ratniece, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
21st century higher education paradigm is based on the teacher-student mutual cooperation, which urges for personalized treatment of students, greater cooperation and better links between formal and non-formal education, which can largely be implemented by school learning using digital technologies. Very important are academics skills, including digital literacy, improving the quality and modern teach their subjects. They have to learn new teaching methods, forms, students develop a host of innovative thinking. Universities must become effective partners for global development. Only through the proliferation of networks between like-minded alliances can transformation occur at the scale that is immediately needed in order to advance our present global knowledge economy. Our communities must open their eyes to this imminent future and transform their thinking to see universities, not as self-indulgent “people factories,” but as valuable idea generators with vast influence and the potential to manifest technologies and concepts that can change lives the world over.